Do asymmetric terms of trade shocks affect private savings in a transition economy? - Abdur R. Chowdhury (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This paper examines whether terms of trade shocks have an asymmetric effect on private savings in transition economies.A simple three-period framework is developed to show that, in the presence of binding credit constraints in bad states of nature, savings rates can be sensitive to favorable movements in the permanent component of the terms of trade.This result contrasts with the prediction of the conventional consumption-smoothing model.Empirical analysis with a dynamic panel model further confirms that while favorable movements in the permanent component of the terms of trade have an asymmetric effect on private savings, the magnitude of the effect is relatively small.The results are robust for alternative estimators, determinants, and country groupings.
URN:NBN:fi:bof-201408071975
Keywords: F10; E21; P33; 330; transition; private savings; terms of trade